The Central THαβ Immunity Associated Cytokine: IL-10 Has a Strong Anti-Tumor Ability Toward Established Cancer Models In Vivo and Toward Cancer Cells In Vitro - Hu, Wan-Chung (Frontiers in Oncology, 2021)
Immunotherapy is a promising new approach for cancer treatment. In this study, we propose to use the TH-αβ mediated immune response for cancer treatment. The THαβ-mediated immune response is activated by IL-10 and IL-15. Thus, we used IL-10 and-15 as therapeutic agents in the 4T1 cell line, which is a mouse cell line of breast cancer, and the NXS2 cell line, which is a mouse cell line of neuroblastoma. Cells from 4T1 and NXS2 were subcutaneously inoculated in wild type BALB/c female mice and AJ mice, respectively, and administered cytokines or an antibody treatment at various dosages. Our results showed that IL-10 and IL-15 administration led tore-duction in tumor volume and increase in survival. However, traditional TH1 cytokine IFNg administration led to increase in tumor volume and decline in survival. Antibody treatment in conjunction with IL-10 was not significantly better than IL-10, due to the expression of GD2 on immune cells. Moreover, an anti-GD2 antibody inhibited the immune cells themselves. Addi-tionally, we found that IL-10 was directly toxic to tumor cells in vitro. Thus, we conclude that the THαβ immunological pathway is a good treatment strategy for cancer.